EMANFAATAN CERUK SIREBI SEIWU SEBAGAI TEMPAT PENGUBURAN DI KAMPUNG KAMARISANO DISTRIK WAPOGA KABUPATEN WAROPEN - Sonya M. Kawer (BALAI ARKEOLOGI PAPUA, 2011)
Burial is one of the ways in which to place the corpse. Community in Kampung Kamarisano also recognize the existence of burial is entered in the niche. From the results obtained in the form of niche burial Sirebi Seiwu human skull and some other human bones found on an irregular hole in the niche.